A pilot project to store carbon as biomass in African woodlands. Issue 2 (December 2010) - Grace, J; Ryan, CM; Williams, M; Powell, P; Goodman, L; Tipper, R
Capturing carbon by planting trees or avoiding deforestation is thought to be a cost-effective way to reduce the inexorable rise in CO2 in the atmosphere. We describe a way to motivate African farmers to plant trees and protect woodland, based on a Mozambican pilot project in the voluntary carbon market. By late 2009, 1510 farmers were enrolled. Between 2003 and 2009, the project was able to sell carbon credits totaling approximately US1.3 million on the voluntary carbon market, corresponding to 156, 000 tCO2, at a price that averaged US9.0 per ton. Moreover, the effect of the carbon project was to increase rural employment from 8.6 to 32%, whilst 73% of households raised commercial crops compared with 23% previously. There was also a notable development of social capital, with a measurable increase in literacy and the development of a business ethos with associated practical skills.